DEVELOPMENT OF TEACHERS’ PEDAGOGICAL SKILLS AND TEACHING STYLES ON CLASSROOM MANAGEMENT - A.P. Xujamkulov; N.Raxmonova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. The most valuable present someone can receive is knowledge. Humans are not born knowing. Knowledge is acquired by humans via education and experience.From ancient times to the present, there has been a significant shift in how people learn.The approach that was once employed in educational institutions to acquire knowledge is no longer relevant.Any teacher should able to educate the people if they have a knowledge. When we talk about education, we’re talking about the field that studies how people learn and teach in formal educational settings rather than through unofficial or non-formal media.Education can take many different forms and is the transfer of knowledge, skills, and character qualities.In the past, teaching was mostly teacher-centered, but it has since changed to be student-centered.Different teaching philosophies and methods are now evident in the teaching and learning process.